Ressentiment, I-Conception and Armenophobia in Azerbaijan - Sargsyan, Armen (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
In recent decades, Azerbaijan implements state policy of Armenophobia that has many manifestations in almost all spheres of life. The author proves in the article that success in dissemination of the Armenophobia can be explained on the basis of several factors, including the ressentimentalism and ethnic (national) I-conception of the Azerbaijanians. The latter are manipulated by the Azerbaijanian state authorities that through successful introduction of the enemy image (Armenians) have as a goal the justification of the existing problems in Azerbaijan by the activity of foreign enemies.